Indonesian Prison System: An Analysis of Constitutive Penology Amidst the Crisis of Overcapacity Based on Islamic Law - Didik Purnomo (Justice Law Review, 2025)
The Indonesian correctional system normatively emphasizes prisoners' rehabilitation and social reintegration as stipulated in Law Number 22 of 2022 on Corrections. However, its implementation still faces serious challenges due to a lack of a strong philosophical foundation. Rehabilitation programs tend to be formalistic and uniform, without considering the social context or the individual needs of prisoners. This study aims to reassess the philosophical foundations of the Indonesian correctional system through a theoretical approach to constitutive penology. The research is conducted using a qualitative approach with a literature study method. Data is analyzed descriptively-analytically through a review of legal literature, philosophy, and critical penology. The theory of constitutive penology is used as an analytical tool to understand corrections as a product of social relations and power structures, rather than merely an administrative legal mechanism. The research findings indicate that the Indonesian correctional system does not fully reflect rehabilitation values. Social reintegration is still understood narrowly and does not involve the community in the social recovery process. This study concludes that the reform of the correctional system must begin with a holistic philosophical reconstruction, oriented towards restoring dignity and equally and sustainably involving the social participation of ex-convicts.